2020
DOI: 10.1101/2020.05.14.094722
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phagosome resolution regenerates lysosomes and maintains the degradative capacity in phagocytes

Abstract: Abbreviations: Arl 8: Arf-like GTPase 8, CLC-GFP: GFP-fusion of the clathrin-light chain; ConA: concanamycin A; DQ-BSA: dye-quenched bovine serum albumin; IKA: ikarugamycin; LAMP1: lysosomal-associated membrane protein 1; LAMP2: lysosomal-associated membrane protein 2; LB: Luria-Bertani medium; Lp: Legionella pneumophila; mTORC1: mechanistic target of rapamycin complex 1; PDV: phagosome-derived vesicle; PtdIns(3)P: phosphatidylinositol 3-phosphate; PtdIns(3,5)P 2 : phosphatidylinositol 3,5-biphosphate; PtdIns(… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 103 publications
(194 reference statements)
0
10
0
Order By: Relevance
“…Phagocytosis proceeds in stages which include enveloping of extracellular material by the phagocytic cup, packaging into a phagosome, fusion to mature lysosomes to form a phagolysosome, and resolution of the phagolysosome by fragmentation 67, 68 . Our data suggested that multiple stages of phagocytosis might be regulated by the interferon stimulated genes expressed in cluster 8.…”
Section: Resultsmentioning
confidence: 99%
“…Phagocytosis proceeds in stages which include enveloping of extracellular material by the phagocytic cup, packaging into a phagosome, fusion to mature lysosomes to form a phagolysosome, and resolution of the phagolysosome by fragmentation 67, 68 . Our data suggested that multiple stages of phagocytosis might be regulated by the interferon stimulated genes expressed in cluster 8.…”
Section: Resultsmentioning
confidence: 99%
“…Less is known about the final stage of phagosome resolution and how the phagosome is resorbed to allow the phagocyte to return to homeostasis. However, studies have shown that bacteria‐containing phagolysosomes in macrophages undergo fragmentation through vesicle budding and constriction (Levin et al , 2016 ; Botelho et al , 2020 ; preprint: Lancaster et al , 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Macrophages engulf cargos into lysosomes, where the abundant enzymes can quickly degrade the exogenous materials, including DNA. [ 12 ] They are also non‐dividing cells and lack of virus receptors, [ 13 ] and thus their gene transfection is inefficient even by virus vectors. Exogenous DNA transfection in macrophages is thus inherently challenging.…”
Section: Methodsmentioning
confidence: 99%